Evaluasi Perencanaan Dermaga (Jetty) Pada Pelabuhan Dili Timor Leste - Teodósio Gil Soares da Costa; Putu Ariawan; Komang Agus Ariana (Jurnal Ilmiah Telsinas, 2020)
The jetty is an important facility for a port to support its operational activities. The construction of the jetty at the port of Dili, East Timor is to serve the crossing from Dili to Oecusse, Atauro and vice versa. This jetty has a length of 100 m and a width of 20 m which is a prestressed concrete jetty.The Section of evaluation for jetty plan at Dili Port, East Timor are: the supper structure of the jetty includes among others fender, bollard, vehicle floor plate, and prestressed beam as soon as the sub structure of the jetty there is a poer and pile foundation. Analysis in evaluation structure is based on SNI T-02-2005, SNI 1727: 2013, SNI 2052-2014 and SAP 2000 with the quality of concrete f’c 30 Mpa and the quality of steel reinforcement f’y 400 Mpa.Based on the evaluation for jetty plan at Dili Port, East Timor, is obtained on the dimension of the jetty plate are 30 cm thick with reinforcement direction pedestal x and y equal to = 0,075, while the dimension of the prestressed beam are 70 cm wide and 90 cm high reinforcement pedestal direction x and field direction x equal to ? = 0,066. Poer is planned to be a single unit (monolith) with a pile, while the dimensions of the pile are 45 cm in diameter, 1,2 cm thick and 42,50 m in length. On the berthing structure is used a rubber fender tipe seibu V with a V-300 H capacity, and the mooring structure used is a bent bollard with a capacity of 25 tons.